DE VÍTIMAS A INDICIADOS, UM PROCESSO DE PONTA-CABEÇA: SURUÍ AIKEWÁRA VERSUS DIVINO ETERNO – LAUDO ANTROPOLÓGICO - JANE FELIPE BELTRÃO; LUIZA DE NAZARÉ MASTOP-LIMA; HÉLIO LUIZ FONSECA MOREIRA (Espaço Ameríndio, 2008)
ABSTRACT: Discussion of conflicts arising from infra-structure projects in state and federalroads which cross Indian Territory Sororó (AIS), land of the Suruí Aikewára, in southeast Pará,Brazil. After 30 years of inconvenience caused by the OP-2 later PA-253 and currently BR-153opened by the Brazilian Army at the time of conflict with those fighting in the Araguaia Guerrilla,the Suruí Aikewára, with the aid of Federal Attorney Office, anthropological expert opinion andenvironmental impact study (EIA), to settle the matter with the Pará State Government to mitigatelosses due to the road construction. Some of the items of the agreement, though, have not beencomplied with despite of the Federal Attorney Office mediation – a fact of great dislike to theIndian population who have been left with no other option, but to protest by closing the road onceand again, in attempts to call attention of the State authorities. During the latest of the protests inMarch 2003 – provoked by the finding of a corpse in Indian Territory –truck driver, Divino Eterno,ran into young Surui who obstructed the road and protected the entrance to their village. In defenseof those threatened, the Indians in the scene, detained the driver and his female companion at thetime. Much to the dislike of the Indians and against their will – especially that of the Indianmothers who had their children threatened by the driver action -, the detainees were released byFunai (Indian National Foundation) representatives. Once free, Divino Eterno registered acomplaint at São Geraldo Police Station against three Suruí Aikewará. The action of Funairepresentatives has generated an upside down trial by reversing the position of the Indians fromvictims to the status of defendants.RESUMO: Após 30 anos de incômoda convivência com a estrada estadual, antes conhecida comoOP–2, posteriormente PA–253 e hoje BR–153, aberta pelo exército brasileiro à época daGuerrilha do Araguaia, os Suruí Aikewára conseguiram com auxílio da Procuradoria daRepública estabelecer, mediante laudo antropológico e estudos de impacto ambiental, “acordo”com o Governo do Estado do Pará para mitigar o impacto da rodovia. Entretanto, as cláusulas danegociação não vêm sendo cumpridas, fato que gera descontentamento entre os índios. Os Suruí,premidos pelos problemas causados pela rodovia, não possuem outro recurso que “entupedinir”(obstruir) a rodovia, vez por outra, para chamar atenção das autoridades. À última manifestaçãode descontentamento em março de 2003, provocada pela descoberta de mais um cadáver“despejado” em suas terras, o caminhoneiro de nome Divino Eterno ultrapassou os obstáculos eatirou o veículo sobre os jovens Suruí que guarneciam a obstrução da rodovia. Na defesa de seuterritório e na ausência de autoridades constituídas, os guerreiros retiveram o veículo, o motoristae a mulher que o acompanhava. Depois de algum tempo, a “liberação” dos retidos e do veículopelos representantes do órgão tutelar, à revelia dos Suruí, possibilitou que, liberado, DivinoEterno oferecesse queixa, na delegacia de São Geraldo do Araguaia, contra três Suruí Aikewára. Aação dos representantes da FUNAI gerou um processo de ponta-cabeça, posto que de vítimas(agredidos) os Suruí passaram a indiciados (agressores).